Review Paper on Experimental Studies on Ferrocement: Examining the Technical Parameters and Benefits of Ferrocement Technology (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ferrocement is composite material of cement matrix and reinforcement having multiple layers of mesh. Ferrocement technologies are mostly used these days in many countries. These are associated with the features such as mechanical properties, advantages, design parameters, research and development, applications, and safety and economy factors. Ferrocement almost covered large scale in construction industries in many countries which gives helps to improve the GDP rate in construction sector. Though the use of ferrocement technology is at higher percentage but is does not tackled over the conventional cement and not being used at domestic level. This study deals with technicalparameters regarding the loads and deflection over an effective span by using ferrocement and self-compacting mortar (SCM) with varied wc ratio, mix design criteria and materials which will help to overcome the difficulties and problems in construction.